2018
DOI: 10.1097/cmr.0000000000000471
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients with a pretransplant history of early-stage melanoma

Abstract: A history of melanoma within the preceding 5 years is commonly considered a contraindication to solid organ transplantation. We investigated how a pretransplant history of melanoma impacts patient survival and melanoma recurrence. Institutional Review Board approval was obtained, and Duke's retrospective database was used to identify 4552 patients who underwent a solid organ transplant at Duke University from 1 January 2001 to 31 December 2016. Data with regard to the transplant, melanoma characteristics, reje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…For example, a study of 12 patients with a pretransplant history of early‐stage melanoma and a median period between melanoma diagnosis and organ transplantation of 4.1 years found that two of these patients had developed new melanoma lesions after a median 5.3 years, with these lesions regarded as de novo tumors . Both of these patients were successfully treated by wide local excision . By contrast, we could not identify any study regarding the management of EHM diagnosed shortly before LDLT.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…For example, a study of 12 patients with a pretransplant history of early‐stage melanoma and a median period between melanoma diagnosis and organ transplantation of 4.1 years found that two of these patients had developed new melanoma lesions after a median 5.3 years, with these lesions regarded as de novo tumors . Both of these patients were successfully treated by wide local excision . By contrast, we could not identify any study regarding the management of EHM diagnosed shortly before LDLT.…”
Section: Discussionmentioning
confidence: 80%
“…Few studies have evaluated post‐transplant outcomes in patients with a pretransplant history of EHM . For example, a study of 12 patients with a pretransplant history of early‐stage melanoma and a median period between melanoma diagnosis and organ transplantation of 4.1 years found that two of these patients had developed new melanoma lesions after a median 5.3 years, with these lesions regarded as de novo tumors . Both of these patients were successfully treated by wide local excision .…”
Section: Discussionmentioning
confidence: 99%
“…Only five studies reporting recurrent melanomas indicated that these were metastases, 37,40–42,52 two studies 53,54 specified that the post‐transplant lesion occurred at the same anatomical site as the pre‐transplantation melanoma and the remaining eight studies, seven of them registry‐based, did not indicate whether the post‐transplantation melanoma was a recurrent tumor or a de novo melanoma. Of the four studies stating that the post‐transplantation melanomas were new lesions, two 55,56 specified that the tumors were in different anatomical locations from the pre‐transplantation primary lesions and two 32,50 did not specify how they determined that the lesions were new melanomas. To summarize the patient‐level data; nine patients had recurrences of the same lesion, four had metastases and 59 were unspecified melanoma “recurrences.” Three patients’ lesions were new, developing at a different anatomical site relative to the primary, and 13 were designated as new but not further detailed.…”
Section: Resultsmentioning
confidence: 99%
“…Six patients died of melanoma, but their initial staging was not available. Between 2008 and 2018, four reviews with precise staging data studied pretransplant melanoma [5,8,11,12]. A summary of these studies is presented in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few series of OTR with pretransplant melanoma, either registry studies with many missing data concerning the melanoma, and a few series with complete data but very small patient sample size [5,8–13]. Therefore, these studies cannot provide reliable recommendations concerning the waiting time after melanoma diagnosis, according to the AJCC staging (American Joint Committee on Cancer) [4], after which SOT could be considered safe.…”
Section: Introductionmentioning
confidence: 99%